HLA and Risk of Diffuse Large B cell Lymphoma After Solid Organ Transplantation. Issue 11 (November 2016) - Hussain, Shehnaz K.; Makgoeng, Solomon B.; Everly, Matthew J.; Goodman, Marc T.; Martínez-Maza, Otoniel; Morton, Lindsay M.; Clarke, Christina A.; Lynch, Charles F.; Snyder, Jon; Israni, Ajay; Kasiske, Bertram L.; Engels, Eric A.
Abstract : Background: Solid organ transplant recipients have heightened risk for diffuse large B cell lymphoma (DLBCL). The role of donor-recipient HLA mismatch and recipient HLA type on DLBCL risk are not well established. Methods: We examined 172 231 kidney, heart, pancreas, and lung recipients transplanted in the United States between 1987 and 2010, including 902 with DLBCL. Incidence rate ratios (IRRs) were calculated using Poisson regression for DLBCL risk in relation to HLA mismatch, types, and zygosity, adjusting for sex, age, race/ethnicity, year, organ, and transplant number. Results: Compared with recipients who had 2 HLA-DR mismatches, those with zero or 1 mismatch had reduced DLBCL risk, (zero: IRR, 0.76, 95% confidence interval [95% CI], 0.61-0.95; one: IRR, 0.83; 95% CI, 0.69-1.00). In stratified analyses, recipients matched at either HLA-A, -B, or -DR had a significantly reduced risk of late-onset (>2 years after transplantation), but not early-onset DLBCL, and there was a trend for decreasing risk with decreasing mismatch across all 3 loci ( P = 0.0003). Several individual recipient HLA-A, -B, -C, -DR, and -DQ antigens were also associated with DLBCL risk, including DR13 (IRR, 0.74; 95% CI, 0.57-0.93) and B38 (IRR, 1.48; 95% CI, 1.10-1.93), confirming prior findings that these 2 antigens are associated with risk of infection-associated cancers. Conclusions: In conclusion, variation in HLA is related to susceptibility to DLBCL, perhaps reflecting intensity of immunosuppression, control of Epstein-Barr virus infection among transplant recipients or chronic immune stimulation. Abstract : The risk of diffuse large B cell lymphoma after solid organ transplant recipients is significantly reduced with decreasing mismatch across all 3 HLA loci. This finding reflects intensity of immunosuppression, control of Epstein-Barr virus infection among transplant recipients or chronic immune stimulation. Supplemental digital content is available in the text.